Manual Compared With Electric Vacuum Aspiration for Treatment of Molar Pregnancy - Padron, Lilian; Rezende Filho, Jorge; Amim Junior, Joffre; Sun, Sue Yazaki; Charry, Rafael Cortes; Maesta, Izildinha; Elias, Kevin M.; Horowitz, Neil; Braga, Antonio; Berkowitz, Ross S. (Lippincott Williams & Wilkins, 2018)
OBJECTIVE: To evaluate uterine evacuation of patients with molar pregnancy, comparing manual with electric vacuum aspiration. METHODS: This is a retrospective cohort study of patients with molar pregnancy followed at the Rio de Janeiro Trophoblastic Disease Center from January 2007 to December 2016. The individual primary study outcomes were incomplete uterine evacuation, uterine perforation, development of uterine synechia, and development of postmolar gestational trophoblastic neoplasia. Secondary endpoints were other features of the perioperative outcomes (operative time, rate of transfusion, hemoglobin change, length of stay) and the clinical course of neoplasia (Prognostic Risk Score, presence of metastases, time to remission, and need for multiagent chemotherapy). RESULTS: Among 1,727 patients with molar pregnancy, 1,206 underwent electric vacuum aspiration and 521 underwent manual vacuum aspiration. After human chorionic gonadotropin normalization, patients with benign molar pregnancy were followed for 6 months and patients treated for gestational trophoblastic neoplasia were followed for 12 months. Baseline risk factors for gestational trophoblastic neoplasia and demographic features were similar between the treatment groups. Uterine synechia developed less frequently after manual vacuum aspiration than after electric vacuum aspiration, 6 of 521 vs 63 of 1,206 (adjusted odds ratio [OR] 0.21, 95% CI 0.09-0.49), despite no differences in the occurrence of incomplete uterine evacuation, 65 of 521 vs 161 of 1,206 (adjusted OR 0.93, 95% CI 0.69-1.27), development of postmolar gestational trophoblastic neoplasia, 90 of 521 vs 171 of 1,206 (adjusted OR 1.26, 95% CI 0.96-1.67), or the need for multiagent chemotherapy, 22 of 521 vs 41 of 1,206 (adjusted OR 0.81, 95% CI 0.73-1.28). CONCLUSION: Manual vacuum aspiration appears to be similar to electric vacuum aspiration for treatment of molar pregnancy and may be associated with less development of uterine synechia.